Governance of flood management framework in Malaysia - Maidin, Siti Sarah; Arshad, Noor Habibah; Othman, Marini (American Sceintific Publishing, 2018)
This study proposes a governance framework to govern the flood management in Malaysia. Respondents involving directly in flood management have been interviewed in order to construct a governance framework on flood management comprising of seventeen (17) building blocks components. Based on the process and activities involved in each component, Malaysian flood management agencies are able to incorporate governance practices into their operations.